Microbacterium proteolyticum sp nov isolated from roots of Halimione portulacoides - Alves, Artur
An endophytic actinobacterial strain RZ36T, isolated from roots of the salt-marsh plant Halimione portulacoides, was subjected to a polyphasic taxonomic characterization. 16S rRNA gene sequence analysis revealed that this strain belonged to the genus Microbacterium. The closest phylogenetic relative was Microbacterium hominis DSM 12509T, with a pairwise 16S rRNA gene sequence similarity of 98.8 %. The DNA–DNA hybridization value between strain RZ36T and M. hominis DSM 12509T was 16 %. The affiliation to the genus Microbacterium was corroborated by phenotypic and chemotaxonomic characteristics. The cell-wall peptidoglycan type was B2b and the diagnostic diamino acid was ornithine. Whole-cell sugars detected were galactose, glucose, rhamnose, ribose and xylose. The major fatty acids were anteiso-C15 : 0 and iso-C16 : 0 and the major menaquinone was MK-11 (64 %). Main polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol and two unknown glycolipids. The genomic DNA G+C content was 69.7 mol%. Thus, on the basis of phenotypic, genotypic and chemotaxonomic data, strain RZ36T is considered to represent a novel species of the genus Microbacterium, for which the name Microbacterium proteolyticum sp. nov. (type strain RZ36T5DSM 27100T5CECT 8356T) is proposed.